2011
DOI: 10.1111/j.1438-8677.2011.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4‐phosphate is associated to extracellular lipoproteic fractions and is detected in tomato apoplastic fluids

Abstract: We have recently detected phosphatidylinositol-4-phosphate (PI4P) in the extracellular medium of tomato cell suspensions. Extracellular PI4P was shown to trigger the activation of defence responses induced by the fungal elicitor xylanase. In this study, by applying a differential centrifugation technique, we found that extracellular PI4P is associated with fractions composed of diverse phospholipids and proteins, which were pelleted from the extracellular medium of tomato cell suspensions grown under basal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…2E, G), which cleaves phospholipids into their lipophilic and hydrophilic components. Therefore, almost certainly, the lipid layer on vessels at least partially consists of phospholipids, which have been found in xylem sap (Gonorazky et al, 2012;Schenk et al, 2017). Under TEM, this same lipid layer along vessel walls appears broken up into black OsO 4 -stained nanoparticles (Fig.…”
Section: Vessel Lumen Surface Characteristicsmentioning
confidence: 79%
See 1 more Smart Citation
“…2E, G), which cleaves phospholipids into their lipophilic and hydrophilic components. Therefore, almost certainly, the lipid layer on vessels at least partially consists of phospholipids, which have been found in xylem sap (Gonorazky et al, 2012;Schenk et al, 2017). Under TEM, this same lipid layer along vessel walls appears broken up into black OsO 4 -stained nanoparticles (Fig.…”
Section: Vessel Lumen Surface Characteristicsmentioning
confidence: 79%
“…4) had few surprises; carbon and oxygen are components of cellulose and potassium, and calcium, chloride, phosphorus, and sulfur are commonly found in xylem sap. The phosphorus peak observed in Distictis, Geijera, and Encelia could be from inorganic phosphate or organic molecules that contain phosphate groups, including phospholipids (Gonorazky et al, 2012;Schenk et al, 2017) or phosphocholine (Martin and Tolbert, 1983). The sulfur peak in Encelia was remarkable for being apparent only in that one species; it could stem from inorganic sulfate or possibly from proteins.…”
Section: Surfaces Of Bordered Pitsmentioning
confidence: 97%
“…It has also been reported that under certain conditions PIs may occur in the luminal/extracellular leaflets of vesicles or the plasma membrane (Gonorazky et al, 2012(Gonorazky et al, , 2008Kale et al, 2010), although it is currently unclear how PIs would manifest in these locations. Within the membrane, PIs act as regulators of integral membrane proteins or mark membrane areas for the recruitment of peripheral membrane proteins.…”
Section: Pi Modes Of Actionmentioning
confidence: 99%
“…Hence, extracellular lipoprotein particles have been detected in tomato apoplastic fluids. 13 Interestingly, they contain several defense-related proteins (including a leaderless aspartyl protease) and also the phospholipid phosphatidylinositol 4-phosphate, previously shown to trigger the activation of defense responses.…”
Section: Apoplastic Vesicles and Proteins Without Predicted Signal Pementioning
confidence: 99%